PERAN BIMBINGAN KONSELING DALAM MENINGKATKAN LITERASI KEUANGAN SISWA - Fransiskus Gaurifa; Nelan Halawa; Rut Trinitatis Waoma; Kaminudin Telaumbanua (Universitas Nias Raya, 2024)
Financial literacy is one of the essential life skills that students need to possess, particularly vocational high school (SMK) students who are prepared to enter the workforce and participate in social life. The low level of students’ ability to manage personal finances, such as budgeting pocket money, saving, and planning long-term finances, indicates the need for targeted and sustainable educational interventions. This study aims to examine and analyze the role of guidance and counseling services in improving students’ financial literacy at SMK Negeri 1 Toma. This research employs a mixed-method approach with an explanatory sequential design, combining quantitative and qualitative methods. Quantitative data were collected through financial literacy questionnaires distributed to students, while qualitative data were obtained through interviews with guidance and counseling teachers and selected students. The results indicate that guidance and counseling services play a significant role in enhancing students’ financial literacy, particularly in terms of basic financial management understanding and attitudes toward saving habits. However, the application of financial literacy in long-term financial planning remains suboptimal. These findings suggest that guidance and counseling services need to be optimized and more systematically integrated with learning programs and other school activities in order to foster more responsible and sustainable financial behavior among students.